2016
DOI: 10.14417/ap.1079
|View full text |Cite
|
Sign up to set email alerts
|

Risco e regulação emocional em idade pré-escolar: a qualidade das interações dos educadores de infância como potencial moderador

Abstract: A investigação tem demonstrado que as crianças em desvantagem social enfrentam muitos desafios e estão mais vulneráveis a desenvolver dificuldades ao nível da regulação emocional, sendo extremamente relevante identificar fatores protetores que moderem esta vulnerabilidade, de modo a identificar formas de alterar as trajetórias desenvolvimentais. No presente estudo, foi analisado o papel moderador das interações do educador de infância no desenvolvimento da regulação emocional. Os participantes incluíram 345 cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…Similar to the previous studies involving Portuguese preschoolers, in the current study, overall, no significant differences were found between the girls' and the boys' mean behavioral self-regulation levels (Cadima et al, 2019), and the girls showed less labile/negative emotional behaviors than the boys (Cadima et al, 2016). Additionally, the results of the current study are aligned with those of the previous studies that suggested that behavioral self-regulation is related to the emergent literacy skills for both boys and girls (e.g., Montroy et al, 2014;Slot & von Suchodoletz, 2018).…”
Section: Sex-differentiated Pathssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the previous studies involving Portuguese preschoolers, in the current study, overall, no significant differences were found between the girls' and the boys' mean behavioral self-regulation levels (Cadima et al, 2019), and the girls showed less labile/negative emotional behaviors than the boys (Cadima et al, 2016). Additionally, the results of the current study are aligned with those of the previous studies that suggested that behavioral self-regulation is related to the emergent literacy skills for both boys and girls (e.g., Montroy et al, 2014;Slot & von Suchodoletz, 2018).…”
Section: Sex-differentiated Pathssupporting
confidence: 88%
“…The participating children's emotional self-regulation skills were assessed through teachers' reports using the Emotion Regulation Checklist (ERC; Shields & Cicchetti, 1997). Following the measure's authors (Shields & Cicchetti, 1997) and recent studies (e.g., Cadima et al, 2016), in the current study we use two subscales of the ERC. The Lability/Negativity subscale evaluates the teacher's perceptions of the child's mood shifts, dysregulated negative affect, and intensity of emotions and has 11 items (e.g., "Is prone to angry outbursts/tantrums easily").…”
Section: Emotional Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted with socially disadvantaged children in classrooms with early childhood educators who establish high emotional and organizational quality interactions have shown that they reveal higher emotional regulation skills [16]. This result corroborates the perspective of Mestre, Guil, Martinez-Cabanas, Larrán and Gonzales [17] when they assert that the development of the abilities implicit in the perception, expression and valorization of preschool children's emotions depends on the combination of cognitive and socio-emotional development.…”
Section: Introductionsupporting
confidence: 84%
“…Oliveira, Gurtat e Reis (2018),Cadima et al (2016), Santos e Barros (2018), Mendes, Pires e Fioravanti (2017) e…”
mentioning
confidence: 99%